Solvent Influence on the Magnetic Properties of Iron(II) Spin‐Crossover Coordination Compounds with 4, 4′‐Dipyridylethyne as Linker. Issue 13 (15th January 2016) - Dankhoff, Katja; Lochenie, Charles; Puchtler, Florian; Weber, Birgit
Abstract: New iron(II) coordination polymers with solvent‐dependent spin‐crossover behaviour have been synthesised by using an N2 O2 Schiff base like ligand and 4, 4′‐dipyridylethyne as the bridging axial ligand in different solvents. The effects of different solvents and preparation methods (temperature, concentration) on the magnetic properties have been investigated. Annealing the coordination polymers prepared by the same method but in different solvents led to the same compound exhibiting the same three‐step spin crossover independent of the magnetic properties of the solvated species. The X‐ray structures of the axial ligand, an iron(II) dimer and one of the iron(II) coordination polymers are discussed. Powder X‐ray diffraction analysis was additionally used for further comparison of the compounds. Abstract : Different solvates of an iron(II) coordination polymer have been prepared. Although the spin‐crossover properties of the different solvated forms are different, after removal of the solvent the same three‐step spin transition is observed.